The coming of the Mundane Cyborg La llegada del Ciborg Mundano - Steven Mentor (Revista Teknokultura, 2011)
A number of scholars have attempted to outline both a field of “cyborgology” and a set of dominant concerns and tropes concerning the phenomena of accelerating human-machine hybrids. This article argues that, in contrast to popular conceptions of cyborgs as extreme, posthuman monsters, the cyborg concept can be usefully applied to mundane technologies such as automobiles, and that the proliferation of these “mundane cyborgs” is an important consideration in theorizing the cyborg. The essay offers some definitions and typologies of cyborgs, and applies these to the notion that automobiles are exoskeletons with cyborgian consequences. Varios estudiosos han perfilado la “ciborgología” como el conjunto de las principales reflexiones sobre el fenómeno de la hibridización acelerada entre humanos y máquinas. Este artículo sostiene que a diferencia de las imágenes populares de los ciborgs, en las que prevalecen representaciones exageradas de monstruos poshumanos, el concepto es extensible a las tecnologías cotidianas, como los automóviles. También se plantea que la proliferación de estos "ciborgs mundanos" supone un hito de máxima importancia en la propia ciborgología. Para apoyar esta idea propongo algunas definiciones y tipologías de los ciborgs en las que me baso para argumentar que los automóviles, ejemplo de ciborg mundano, son exoesqueletos con consecuencias “ciborgizantes